Localização de terminais intermodais na rede de escoamento da soja em grão brasileira destinada à exportação - Almeida, Marina Soares (2010)
Soybean is one of the most important agricultural products grown in Brazil. Comparing to the total volume of grain produced, soybean corresponds to approximately 44% and the midwest region is the largest soybean producer in Brazil. Because of that, the soybean that goes for export, on average, have to go over large distances to reach the maritime ports from where it is exported. Transport costs represent approximately 25% of the total cost what influences directly on the product price in international market. Loading transportation over long distances, such as the Brazilian soybean flows, the intermodal transportation is an alternative to make the soybean flows for export more economical. The efficient loading transportation using more than one modal depends not only on the availability of the transport itself but also on support infrastructure, such as intermodal terminals. In order to support decisions regarding the design and operation of the network flow of soybean for export, this work proposes using a mathematical programming model based on the Theory of Facilities Location to locate intermodal terminals in the network, taking into account not only the physical network, but also flows of soybeans that are moved by its vertices and arcs. We made several computational preliminary tests to verify the adequacy of the model to the reality we want to represent. Given the adequacy of the model, new experiments were done on a network that represents more realistically the present situation of the soybean flows in Brazil.